Theories of inflation: basic approaches and concepts ("Journal "U". Economy. Management. Finance.", 2024)
The study of the presented article is a comparative analysis of classical and Keynesian theories of inflation, and also highlights modern and mixed approaches to this issue.
Keywords: inflation; Keynesian theory; classical theory; approaches to the theory of inflation